Assessment of fluctuations of the long-term runoff in the Shu-Talas river basin (Journal of Geography and Environmental Management, 2019)
In the article is analyzes long-term fluctuations in the runoff of the Shu-Talas river basin. In theirver basin connection with the lack of data in the series of observations for the selected calculationperiod, the hydrological data of the series were restored by using the method of recalculatedanalogs.The homogeneity series of the river basin was estimated by using the modern StokStat program, aswell as Student, Fisher, Wilcoxon criterias. Long-term runoff fluctuations were determined by variousmethods, in particular, the difference integral curves, the number of series, the generalization of years ofdifferent probability. Fluctuations in the runoff are calculated by the method of the probability of occurrenceof a average water ages.The study of fluctuations in river runoff is a very difficult task, it has great scientific and practicalsignificance. Long-term fluctuations in river runoff directly depend on the flowforming factors, and therivers have been classified into several types of feeding of rivers. For river basins covering large areas andlocated on different physical and geographical conditions, the study of cyclic fluctuations in the runofflayer was carried out on the basis of observation materials.Evaluation of long-term fluctuations of the Shu-Talas river basin is of great importance for water supplyof settlements, water management facilities, recreational areas of the region.